moral expert is an important but unknown concept in Hume's moral philosophy and its correspondence with the familiar approach of the "true judge" in Hume's aesthetics - Zolfaghar Hemmati (Journal of Philosophical Investigations, 2022)
In contemporary ethics, moral expert as a person who can recognize sound behaviors in complex situations and be the ideal moral agent. This matter is not new and can be found in Hume's moral philosophy, but it is not as well-known as it should be. If we look at Hume's works, not only we will find a lot of evidence in this issue, but also there is correspondence between it and the true judge, the famous doctrine of Hume’s aesthetics. As there is true judge as a person in aesthetics that with Strong sense, delicate sentiment, practice, comparison, and free from all prejudice Gains general principles of art and recognizes real beauty; In morality, there is a man of temper, preserve himself from illusions, has the command of himself and can separate feelings in complex situations. he determines the right behavior, virtue, and vice. Also, both true judge and moral expert recognize common mistakes and are considered as ideal figures.